THE ROLE OF LEGISLATIVE REGULATION OF AVIATION TRANSPORT INFRASTRUCTURE DEVELOPMENT - Polishchuk, Inna; Blagodatova, Vitalina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: development of theoretical principles and scientific and practical recommendations on the state of improvement of legislative regulation of air transport infrastructure development in Ukraine. Research methods: the paper uses general methods of scientific knowledge, due to the purpose and objectives of this study, namely: logical generalization, analysis and synthesis, comparison and systems approach, as well as comparative law and system-structural methods. Results: the article highlights the current realities, novelties and problems of legislative regulation of trends in air transport infrastructure in Ukraine, identifies areas for improvement of relevant legislation at the present stage of development of the air transport industry, taking into account European integration and globalization, and also concluded that the current state of development of air transport infrastructure in Ukraine in the context of exacerbation of external and internal contradictions, lack of finances and resources, requires the state to take the most effective measures using international experience in reforming this area and applying appropriate strategic decisions. Discussion: modernization and reform of air transport infrastructure in Ukraine in the context of European integration requires further improvement of its legal regulation, legislative support for its sustainable development through a balanced combination of public and private interests, effective air transport policy, state support of domestic airlines and enterprises, deregulation. projects of aviation activity, liberalization of the air transport industry, etc. It is necessary to understand the role of legislative regulation of air transport infrastructure development in the current conditions of reforming the air transport system of Ukraine in the context of European integration and globalization processes. air transport network.